A drug‐repositioning screen for primary pancreatic ductal adenocarcinoma cells identifies 6‐thioguanine as an effective therapeutic agent for TPMT‐low cancer cells. Issue 9 (29th August 2018) - Kim, Inki; Choi, Yeon‐Sook; Song, Jae Hwi; Choi, Eun A; Park, Sojung; Lee, Eun Ji; Rhee, Je‐Keun; Kim, Song Cheol; Chang, Suhwan
Abstract : Pancreatic cancer is one of the most difficult cancers to cure due to the lack of early diagnostic tools and effective therapeutic agents. In this study, we aimed to isolate new bioactive compounds that effectively kill pancreatic ductal adenocarcinoma (PDAC) cells, but not untransformed, human pancreatic ductal epithelial (HPDE) cells. To this end, we established four primary PDAC cell lines and screened 4141 compounds from four bioactive‐compound libraries. Initial screening yielded 113 primary hit compounds that caused over a 50% viability reduction in all tested PDAC cells. Subsequent triplicate, dose‐dependent analysis revealed three compounds with a tumor cell‐specific cytotoxic effect. We found that these three compounds fall into a single category of thiopurine biogenesis. Among them, 6‐thioguanine (6‐TG) showed an IC50 of 0.39–1.13 μm toward PDAC cells but had no effect on HPDE cells. We propose that this cancer selectivity is due to differences in thiopurine methyltransferase (TPMT) expression between normal and cancer cells. This enzyme is responsible for methylation of thiopurine, which reduces its cytotoxicity. We found that TPMT levels were lower in all four PDAC cell lines than in HPDE or Panc1 cells, and that knockdown of TPMT in HPDE or Panc1 cells sensitized them to 6‐TG. Lastly, we used a patient‐derived xenograft model to confirm that 6‐TG has a significant antitumor effect in combination with gemcitabine. Overall, our study presents 6‐TG as a strong candidate for use as a therapeutic agent against PDAC with low levels of TPMT. Abstract : The 5‐year survival of patients with pancreatic ductal adenocarcinoma (PDAC) has been less than 10% for the past three decades, mainly due to the lack of effective therapeutic agents. We screened 4141 bioactive compounds in four different primary PDAC cells to identify novel therapeutic agents. Of these compounds, 6‐thioguanine was the most effective: it exhibited an IC50 of 1 μmol against PDAC cells and did not affect normal human pancreatic ductal epithelial cells at concentrations up to 10 μmol.